Mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser carving master batch as well as preparation method and application thereof

By preparing the modified CACO3 particles and the MG (OH) 2 particles, the mildew, antibacterial antibacterial and halogen -free flame -free PC/ABS radiac feed mother particles, the traditional PC/ABS alloy products are easy to breed bacteria and mold and the problem of fuzzy logo, and achieved it. Materials wide -spectrum antibacterial antibacterial, flame retardant and laser carving effects.

CN119350828AActive Publication Date: 2025-01-24JIANGXI HONGYI POLYMERIC MATERIALS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411499402.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Traditional PC/ABS alloy products are prone to breed bacteria and molds at a certain temperature and humidity, and the printing or spraying marks are prone to blur, resulting in difficulty in identification.

Method used

Use 2 particles, modified Mg (OH) particles, modified inorganic anti-mildew antibacterial agents, modified laser absorptions, dispersion, anti-oxygen, dispersing laser absorption, dispersion, dispersion Mold -proof antibacterial antibacterial and halogen -free flame -retardant PC/ABS radiac feed female grains composed of agents, lubricants and plasticizers are prepared through extrusion.

Benefits of technology

This material has excellent broad -spectrum antibacterial and antibacterial performance, flame retardant performance and good radium carving effect. It is suitable for electronic product shells, switching/button logo, cosmetic packaging materials, internal buttons and instrument panels, machine keyboards/buttons or ors. Safety anti -counterfeiting logo and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104238310000151
    Figure BDA0005104238310000151
  • Figure BDA0005104238310000161
    Figure BDA0005104238310000161
Patent Text Reader

Abstract

The invention provides a mildewproof, antibacterial, halogen-free and flame-retardant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) laser carving master batch as well as a preparation method and application thereof, and relates to the technical field of PC / ABS alloy materials. The mildewproof, antibacterial, halogen-free and flame-retardant PC / ABS laser carving master batch is prepared from the following raw materials in parts by mass: 20 to 70 parts of polycarbonate, 20 to 70 parts of acrylonitrile-butadiene-styrene plastic, 10 to 80 parts of modified CaCO3 particles, 10 to 75 parts of modified Mg (OH) 2 particles, 1 to 5 parts of a modified inorganic mildewproof and antibacterial agent, 0.1 to 8 parts of a modified laser absorbent, 0.2 to 1.0 part of a dispersing agent, 0.1 to 0.5 part of an antioxidant, 0.1 to 1 part of a lubricating agent and 0.2 to 1.0 part of a plasticizer. And the Mg (OH) 2 micro powder subjected to surface modification, the modified inorganic mildew-proof antibacterial agent and the laser absorbent can be uniformly dispersed in the PC / ABS alloy product, so that the mildew-proof antibacterial performance, the flame retardant property and the laser etching effect of the PC / ABS alloy product are effectively and synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PC / ABS alloy materials, and in particular to a mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch and a preparation method and application thereof. Background Art

[0002] PC / ABS alloy is an important engineering plastic that combines the advantages of high strength and high heat resistance of polycarbonate (PC) and easy processing and high impact strength of acrylonitrile-butadiene-styrene copolymer (ABS). It is widely used in the fields of automobiles, electronic devices, chemicals, medicine, biology, etc. With the continuous improvement of people's quality of life, traditional PC / ABS alloy products can no longer meet the needs of safety, health and comfort. For example, traditional PC / ABS alloy products are flammable plastic products (oxygen index (OI) <22%), which cannot meet the fire safety requirements of automobiles and electronic devices. At the same time, traditional PC / ABS alloy products are prone to breed bacteria and mold under the influence of external environments with certain temperature and humidity, causing varying degrees of harm to the environment and human body. In addition, during the storage and transportation of PC / ABS alloy products and long-term contact and friction, it is easy to cause the traditional printed and sprayed logos on the products to be blurred and incomplete, making it difficult to identify. Therefore, it is of great significance to develop new wear-resistant, stable, mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS alloy materials to meet the needs of modern PC / ABS alloy products.

[0003] At present, flame-retardant PC / ABS alloy materials on the market usually use halogen flame retardants, such as bromine flame retardants, which have good effects but high costs and poor environmental protection. In the event of a fire, a large amount of toxic and corrosive hydrogen halide gas will be produced, which will cause great obstacles to escape and fire fighting. In recent years, the industry and academia have been actively developing new flame retardants to replace halogen flame retardants, such as halogen-free flame retardants (phosphorus, nitrogen, inorganic flame retardants), nano flame retardants, etc., to achieve a more environmentally friendly and safer flame retardant effect. In addition to the flame retardant performance requirements, mildew resistance, antibacterial and wear resistance are also another important requirement for modern PC / ABS alloy products. At present, there are two common methods to improve the mildew and antibacterial properties of PC / ABS alloy products: one is to add a certain proportion of organic or natural mildew and antibacterial agents, but such mildew and antibacterial agents are relatively toxic, short-lasting and poor in heat resistance, and are gradually withdrawn from modern PC / ABS alloy products; the second is to add a certain proportion of inorganic metal ion mildew and antibacterial agents (such as silver, copper, zinc ion compounds and titanium oxides, etc.), which have high safety, good mildew and antibacterial properties, heat resistance and chemical stability and are widely used in building materials, coatings, plastics, textiles and other fields. Laser engraving, also known as laser engraving, is a technology that uses a high-energy-density laser beam to etch or mark the surface of a material. Its advantages include fast marking speed, beautiful image marking, high resolution, wear resistance, wide range, low cost, strong anti-counterfeiting, environmental protection, and no need for ink. These advantages make laser engraving an important technology in modern manufacturing, especially in application scenarios that require fine and permanent marking. However, traditional PC / ABS materials have local thermal deformation and color changes during laser engraving and cannot achieve the best laser engraving effect. In order to meet the needs of modern PC / ABS alloy products, technical personnel in this field urgently need to develop a mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch with broad-spectrum mildew-proof and antibacterial properties, flame retardant properties and good laser engraving effect, as well as a preparation method and application thereof. Summary of the invention

[0004] The purpose of the present invention is to provide a mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch and its preparation method and application, so as to solve the problem that traditional PC / ABS alloy products are prone to breeding bacteria and mold under certain temperature and humidity, and the problem that the traditional printed and sprayed marks on PC / ABS alloy products are easy to be blurred and incomplete, making them difficult to identify.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch, which is prepared from the following raw materials in parts by mass:

[0007] 20-70 parts of polycarbonate, 20-70 parts of acrylonitrile-butadiene-styrene plastic, 10-80 parts of modified CaCO3 particles, 10-75 parts of modified Mg(OH)2 particles, 1-5 parts of modified inorganic antifungal and antibacterial agent, 0.1-8 parts of modified laser absorber, 0.2-1.0 parts of dispersant, 0.1-0.5 parts of antioxidant, 0.1-1 parts of lubricant and 0.2-1.0 parts of plasticizer.

[0008] Preferably, the method for preparing the modified CaCO3 particles comprises the following steps: mixing CaCO3 particles, a first surface modifier and a first lubricant to react to obtain modified CaCO3 particles;

[0009] The first surface modifier includes one or more of a silane coupling agent, an aluminate, a titanate coupling agent, and a pentaerythritol stearate coupling agent;

[0010] The first lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, stearic acid and zinc stearate;

[0011] The mass ratio of the CaCO3 particles, the first surface modifier and the first lubricant is 100:0.3-1:0.5-2;

[0012] The reaction temperature is 90-100° C., and the reaction time is 8-15 minutes.

[0013] Preferably, the preparation method of the modified Mg(OH)2 particles comprises the following steps: mixing and reacting the Mg(OH)2 particles, the second surface modifier and the second lubricant to obtain the modified Mg(OH)2 particles;

[0014] The second surface modifier includes one or more of a silane coupling agent, stearic acid, oleic acid, isocyanate, titanate and aluminate;

[0015] The second lubricant includes one or more of N,N'-ethylene bisoleamide, N,N'-ethylene bisstearamide, polyethylene wax and zinc stearate;

[0016] The mass ratio of the Mg(OH)2 particles, the second surface modifier and the second lubricant is 100:0.3-1.5:0.5-2;

[0017] The reaction temperature is 90-110°C, and the reaction time is 7-15 minutes.

[0018] Preferably, the preparation method of the modified inorganic antifungal and antibacterial agent comprises the following steps: mixing the inorganic antifungal and antibacterial agent with a third surface modifier to obtain the modified inorganic antifungal and antibacterial agent;

[0019] The inorganic mildew and antibacterial agent includes one or more of titanium dioxide, tin dioxide, silver oxide, cupric oxide, cuprous oxide, copper sulfate, zinc oxide, and calcium phosphate;

[0020] The third surface modifier includes one or more of a silane coupling agent, a titanate, an aluminate, a phosphate, an isocyanate, a borate, a zinc stearate and a polyethylene wax;

[0021] The mass ratio of the inorganic mildew and antibacterial agent to the third surface modifier is 100:0.5-2.0;

[0022] The reaction temperature is 90-100° C., and the reaction time is 6-15 minutes.

[0023] Preferably, the preparation method of the modified laser absorber comprises the following steps: mixing the laser absorber with a fourth surface modifier to obtain a modified laser absorber;

[0024] The laser absorbent includes one or more of carbon black, mica powder, basic copper phosphate, copper chrome black, tin oxide, titanium oxide, indium oxide, bismuth oxide, phthalocyanine blue and phthalocyanine green;

[0025] The fourth surface modifier includes one or more of silane coupling agent, aluminate, titanate, phosphate, oleate, zinc stearate, and polyethylene wax;

[0026] The reaction temperature is 90-100°C and the reaction time is 8-15 minutes;

[0027] The mass ratio of the laser absorber to the fourth surface modifier is 100:0.3-1.

[0028] Preferably, the dispersant includes one or more of sodium polyacrylate, nonylphenol polyoxyethylene ether phosphate, polyacrylamide, aminosilane and sodium dodecylbenzene sulfonate;

[0029] The antioxidant includes one or more of tert-butylhydroquinone, tea polyphenols, 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, diisooctyl benzene phosphite, triphenyl phosphite and dioctyl benzene phosphite.

[0030] Preferably, the lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, polyethylene wax, paraffin, stearic acid and zinc stearate;

[0031] The plasticizer includes one or more of dibutyl phthalate, dioctyl phthalate, di(2-ethylhexyl) phthalate, tricresyl phosphate, triphenyl phosphate and tri(2-ethylhexyl) phosphate.

[0032] The present invention also provides a method for preparing the mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch, comprising the following steps:

[0033] Polycarbonate, acrylonitrile-butadiene-styrene plastic, modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent, modified laser absorber, dispersant, antioxidant, lubricant and plasticizer are mixed and extruded to granulate to obtain mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch.

[0034] Preferably, the granulation temperature is 210-250° C., the granulation pressure is ≤10 MPa, and the granulation current is 50-110A.

[0035] The present invention also provides an application of the mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch in electronic product housings, switch covers / button labels, cosmetic packaging materials, automotive interior buttons and instrument panels, machine keyboards / buttons or security anti-counterfeiting labels.

[0036] The present invention has at least the following beneficial effects:

[0037] The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch provided by the present invention has both excellent broad-spectrum mildew-proof and antibacterial properties and flame-retardant properties and good laser engraving effects, and can be widely used in electronic product housings, switch covers / button logos, cosmetic packaging materials, automotive interior buttons and instrument panels, machine keyboards / buttons or security anti-counterfeiting logos and other fields, and has immeasurable economic and social benefits. DETAILED DESCRIPTION

[0038] The present invention provides a mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch, which is prepared from the following raw materials in parts by mass:

[0039] 20-70 parts of polycarbonate, 20-70 parts of acrylonitrile-butadiene-styrene plastic, 10-80 parts of modified CaCO3 particles, 10-75 parts of modified Mg(OH)2 particles, 1-5 parts of modified inorganic mildew and antibacterial agent, 0.1-8 parts of modified laser absorbent, 0.2-1.0 parts of dispersant, 0.1-0.5 parts of antioxidant, 0.1-1 parts of lubricant, 0.2-1.0 parts of plasticizer; preferably 30-60 parts of polycarbonate, 30-60 parts of acrylonitrile-butadiene-styrene plastic, 20-60 parts of modified CaCO3 particles, 20-55 parts of modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent 2-4 parts of antibacterial agent, 1-7 parts of modified laser absorber, 0.3-0.9 parts of dispersant, 0.2-0.4 parts of antioxidant, 0.3-0.9 parts of lubricant, 0.4-0.8 parts of plasticizer; further preferably, 40-50 parts of polycarbonate, 40-50 parts of acrylonitrile-butadiene-styrene plastic, 30-40 parts of modified CaCO3 particles, 30-45 parts of modified Mg(OH)2 particles, 3-4 parts of modified inorganic antifungal and antibacterial agent, 3-5 parts of modified laser absorber, 0.5-0.7 parts of dispersant, 0.3-0.4 parts of antioxidant, 0.4-0.6 parts of lubricant, 0.5-0.6 parts of plasticizer.

[0040] In the present invention, the preparation method of the modified CaCO3 particles comprises the following steps: mixing CaCO3 particles, a first surface modifier and a first lubricant, and reacting to obtain modified CaCO3 particles.

[0041] In the present invention, the first surface modifier includes one or more of a silane coupling agent, an aluminate, a titanate coupling agent and a pentaerythritol stearate coupling agent.

[0042] In the present invention, the first lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, stearic acid and zinc stearate.

[0043] In the present invention, the mass ratio of the CaCO3 particles, the first surface modifier and the first lubricant is 100:0.3-1:0.5-2, preferably 100:0.4-0.8:0.8-1.8, and more preferably 100:0.5-0.7:1-1.5.

[0044] In the present invention, the reaction temperature is 90-100°C, preferably 92-98°C, more preferably 94-96°C, and more preferably 95°C; the reaction time is 8-15 min, preferably 10-14 min, and more preferably 12-13 min.

[0045] In the present invention, the preparation method of the modified Mg(OH)2 particles comprises the following steps: mixing the Mg(OH)2 particles, the second surface modifier and the second lubricant to obtain the modified Mg(OH)2 particles.

[0046] In the present invention, the second surface modifier includes one or more of a silane coupling agent, stearic acid, oleic acid, isocyanate, titanate and aluminate.

[0047] In the present invention, the second lubricant includes one or more of N,N'-ethylenebisoleamide, N,N'-ethylenebisstearamide, polyethylene wax and zinc stearate.

[0048] In the present invention, the mass ratio of the Mg(OH)2 particles, the second surface modifier and the second lubricant is 100:0.3-1.5:0.5-2, preferably 100:0.5-1.2:0.8-1.8, further preferably 100:0.6-1:1-1.5, and more preferably 100:0.8-1:1.2-1.5.

[0049] In the present invention, the reaction temperature is 90-110°C, preferably 95-105°C, more preferably 98-102°C, and more preferably 100°C; the reaction time is 7-15 min, preferably 8-13 min, and more preferably 10-11 min.

[0050] In the present invention, the preparation method of the modified inorganic antifungal and antibacterial agent comprises the following steps: mixing the inorganic antifungal and antibacterial agent with a third surface modifier to obtain the modified inorganic antifungal and antibacterial agent.

[0051] In the present invention, the inorganic mildew and antibacterial agent includes one or more of titanium dioxide, tin dioxide, silver oxide, copper oxide, cuprous oxide, copper sulfate, zinc oxide, and calcium phosphate.

[0052] In the present invention, the third surface modifier includes one or more of a silane coupling agent, a titanate, an aluminate, a phosphate, an isocyanate, a borate, a zinc stearate and a polyethylene wax.

[0053] In the present invention, the mass ratio of the inorganic antifungal and antibacterial agent to the third surface modifier is 100:0.5-2.0, preferably 100:0.7-1.8, more preferably 100:0.9-1.5, and more preferably 100:1.1-1.3.

[0054] In the present invention, the reaction temperature is 90-100°C, preferably 92-98°C, more preferably 94-96°C, and more preferably 95°C; the reaction time is 6-15 min, preferably 8-13 min, more preferably 9-12 min, and more preferably 10 min.

[0055] In the present invention, the preparation method of the modified laser absorber comprises the following steps: mixing the laser absorber with a fourth surface modifier to obtain the modified laser absorber.

[0056] In the present invention, the laser absorbent includes one or more of carbon black, mica powder, basic copper phosphate, copper chromium black, tin oxide, titanium oxide, indium oxide, bismuth oxide, phthalocyanine blue and phthalocyanine green.

[0057] In the present invention, the fourth surface modifier includes one or more of silane coupling agent, aluminate, titanate, phosphate, oleate, zinc stearate and polyethylene wax.

[0058] In the present invention, the reaction temperature is 90-100°C, preferably 92-98°C, more preferably 94-96°C, and more preferably 95°C; the reaction time is 8-15 min, preferably 9-14 min, more preferably 10-13 min, and more preferably 11-12 min.

[0059] In the present invention, the mass ratio of the laser absorbent to the fourth surface modifier is 100:0.3-1, preferably 100:0.3-1, more preferably 100:0.3-1, and even more preferably 100:0.3-1.

[0060] In the present invention, the dispersant includes one or more of sodium polyacrylate, nonylphenol polyoxyethylene ether phosphate, polyacrylamide, aminosilane and sodium dodecylbenzene sulfonate.

[0061] In the present invention, the antioxidant includes one or more of tert-butylhydroquinone, tea polyphenols, 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, diisooctyl benzene phosphite, triphenyl phosphite and dioctyl benzene phosphite.

[0062] In the present invention, the lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, polyethylene wax, paraffin, stearic acid and zinc stearate.

[0063] In the present invention, the plasticizer includes one or more of dibutyl phthalate, dioctyl phthalate, di(2-ethylhexyl) sebacate, tricresyl phosphate, triphenyl phosphate and tri(2-ethylhexyl) phosphate.

[0064] The present invention also provides a method for preparing the mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch, comprising the following steps:

[0065] In the present invention, polycarbonate, acrylonitrile-butadiene-styrene plastic, modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent, modified laser absorber, dispersant, antioxidant, lubricant and plasticizer are mixed, extruded and granulated to obtain mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch.

[0066] In the present invention, the granulation temperature is 210-250°C, preferably 220-240°C, more preferably 225-235°C, and more preferably 230°C; the granulation pressure is ≤10MPa, preferably 3-10MPa, and more preferably 5-8MPa; the granulation current is 50-110A, preferably 60-100A, more preferably 70-90A, and more preferably 80A.

[0067] The present invention also provides an application of the mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch in electronic product housings, switch covers / button labels, cosmetic packaging materials, automotive interior buttons and instrument panels, machine keyboards / buttons or security anti-counterfeiting labels.

[0068] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0069] Example 1

[0070] (1) Preparation of modified CaCO3 particles: 1 kg of CaCO3 powder with a particle size of 2500-3500 mesh was dried at 105° C. for 2 hours for later use. The dried CaCO3 powder, zinc stearate and pentaerythritol stearate coupling agent (manufacturer: Guangdong Jiadele Technology Co., Ltd., label PETS) were added into a temperature-controlled high-speed mixer and mixed at 100° C. and a stirring rate of 500 r / min for 12 min to obtain surface-modified and activated modified CaCO3 particles. The reaction temperature was controlled at 100° C. The amount of zinc stearate was 1.5% of the mass of calcium carbonate, and the amount of pentaerythritol stearate coupling agent was 0.7% of the mass of calcium carbonate.

[0071] (2) Preparation of modified Mg(OH)2 particles: 1 kg of Mg(OH)2 particles with a particle size of 3500-4500 mesh were dried at 105°C for 2 hours for later use. The dried Mg(OH)2 particles, stearic acid and N,N'-ethylene bisstearamide (manufacturer: Changzhou Kesai Chenggong Plastic Material Co., Ltd., label number WAX2003) surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain modified Mg(OH)2 particles. The reaction temperature was controlled at 100°C. The amount of stearic acid was 1.0% of the mass of Mg(OH)2, and the amount of N,N'-ethylene bisstearamide was 1.1% of the mass of Mg(OH)2.

[0072] (3) Preparation of modified inorganic antifungal and antibacterial agent: 0.5 kg of silver oxide was dried at 105°C for 2 hours for later use. The dried silver oxide (manufacturer: Xilong Science Co., Ltd.) and titanate (manufacturer: Nanjing Tengchuan Technology Co., Ltd., label TC-130) and polyethylene wax (manufacturer: Hubei Boshi Chemical Co., Ltd., label R-110) surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain a modified inorganic antifungal and antibacterial agent. The reaction temperature was controlled at 95°C. The amount of titanate was 0.8% of the mass of silver oxide, and the amount of N,N'-ethylene bisstearamide was 0.9% of the mass of silver oxide.

[0073] (4) Preparation of modified laser absorber: 0.5 kg of phthalocyanine blue was dried at 105°C for 2 hours for later use. The dried phthalocyanine blue (manufacturer: Yuhong Pigment Co., Ltd., label PB15:3) and titanate (manufacturer: Nanjing Tengchuan Technology Co., Ltd., label TC-130) surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain the modified laser absorber. The reaction temperature was controlled at 95°C. The amount of titanate used was 0.7% of the mass of phthalocyanine blue.

[0074] Preparation of anti-mildew, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch:

[0075] According to the mass percentage, weigh 14 parts of polycarbonate (manufacturer: Jiangsu Dingchengxin Engineering Plastics Co., Ltd., label PC GP1000ML), 6 parts of acrylonitrile-butadiene-styrene plastic (manufacturer: Shanghai Heyiyuan Plastic Raw Materials Co., Ltd., label ASG-30), 20 parts of modified CaCO3 particles, 51 parts of modified Mg(OH)2 particles, 3 parts of modified silver oxide, 4 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly, and then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0076] Example 2

[0077] (1) Preparation of modified CaCO3 particles: 1 kg of CaCO3 powder with a particle size of 2500-3500 mesh was dried at 105°C for 2 hours for later use. The dried CaCO3 powder, N,N'-ethylene bisstearamide and titanate coupling agent were added to a temperature-controlled high-speed mixer and mixed at 95°C and a stirring rate of 500 r / min for 15 minutes to obtain surface-modified and activated modified CaCO3 particles. The amount of N,N'-ethylene bisstearamide was 1.8% of the mass of calcium carbonate, and the amount of titanate coupling agent was 0.5% of the mass of calcium carbonate.

[0078] (2) Preparation of modified Mg(OH)2 particles: 1 kg of Mg(OH)2 particles with a particle size of 3500-4500 mesh were dried at 105°C for 2 hours for later use. The dried Mg(OH)2 particles, silane coupling agent (manufacturer: Yunsheng Chemical (Shandong) Co., Ltd., label KH570) and polyethylene wax surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 10 min to obtain modified Mg(OH)2 particles. The reaction temperature was controlled at 110°C. The amount of silane coupling agent was 1.5% of the mass of Mg(OH)2, and the amount of polyethylene wax was 0.8% of the mass of Mg(OH)2.

[0079] (3) Preparation of modified inorganic antifungal and antibacterial agent: Dry 0.5 kg of calcium phosphate at 105°C for 2 hours for use, add the dried calcium phosphate (manufacturer: Shandong Polychemical Co., Ltd.), aluminate (manufacturer: Wuxi Yiyuan New Material Technology Co., Ltd.) and polyethylene wax surface modifier into a temperature-controlled high-speed mixer and mix at a stirring rate of 600 r / min for 12 min to obtain a modified inorganic antifungal and antibacterial agent. The reaction temperature is controlled at 95°C. The amount of aluminate is 0.8% of the mass of calcium phosphate, and the amount of borate is 0.9% of the mass of calcium phosphate.

[0080] (4) Preparation of modified laser absorbent: 0.5 kg of tin oxide was dried at 105°C for 2 hours for use, and the dried tin oxide (manufacturer: Shandong Hui'an Chemical Co., Ltd.) and oleate (manufacturer: Jiangsu Hai'an Petrochemical Plant, grade polysorbate 80) surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain a modified laser absorbent. The reaction temperature was controlled at 95°C, and the amount of oleate used was 0.7% of the mass of the tin oxide.

[0081] Preparation of anti-mildew, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch:

[0082] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 30 parts of modified CaCO3 particles, 41 parts of modified Mg(OH)2 particles, 3 parts of modified silver oxide, 4 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0083] Example 3

[0084] (1) Preparation of modified CaCO3 particles: 1 kg of CaCO3 powder with a particle size of 2500-3500 mesh was dried at 105°C for 2 hours for later use. The dried CaCO3 powder, N,N'-ethylene bisoleamide and silane coupling agent were added to a temperature-controlled high-speed mixer and mixed at 90°C and a stirring rate of 500 r / min for 15 minutes to obtain surface-modified and activated modified CaCO3 particles. The amount of N,N'-ethylene bisoleamide was 2% of the mass of calcium carbonate, and the amount of silane coupling agent was 0.8% of the mass of calcium carbonate.

[0085] (2) Preparation of modified Mg(OH)2 particles: 1 kg of Mg(OH)2 particles with a particle size of 3500-4500 mesh were dried at 105°C for 2 hours for later use. The dried Mg(OH)2 particles, isocyanate and zinc stearate surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 10 min to obtain modified Mg(OH)2 particles. The reaction temperature was controlled at 110°C. The amount of isocyanate was 0.8% of the mass of Mg(OH)2, and the amount of zinc stearate was 15% of the mass of Mg(OH)2.

[0086] (3) Preparation of modified inorganic antifungal and antibacterial agent: 0.5 kg of copper sulfate was dried at 105°C for 2 hours for later use. The dried copper sulfate and isocyanate were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain a modified inorganic antifungal and antibacterial agent. The reaction temperature was controlled at 95°C. The amount of titanate used was 1.2% of the mass of copper sulfate.

[0087] (4) Preparation of modified laser absorber: 0.5 kg of mica powder was dried at 105°C for 2 hours for later use. The dried mica powder and oleic acid ester surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 15 min to obtain the modified laser absorber. The reaction temperature was controlled at 90°C and the amount of oleic acid ester was 1% of the mass of the mica powder.

[0088] Preparation of anti-mildew, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch:

[0089] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 40 parts of modified CaCO3 particles, 31 parts of modified Mg(OH)2 particles, 3 parts of modified silver oxide, 4 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0090] Example 4

[0091] (1) Preparation of modified CaCO3 particles: 1 kg of CaCO3 powder with a particle size of 2500-3500 mesh was dried at 105°C for 2 hours for later use, and the dried CaCO3 powder was mixed with N,N'-ethylene bisoleamide and silane coupling agent (added to a temperature-controlled high-speed mixer and mixed for 15 minutes at 95°C and a stirring rate of 500 r / min to obtain surface-modified and activated modified CaCO3 particles. The reaction temperature was controlled at 100°C. The amount of N,N'-ethylene bisoleamide was 2% of the mass of calcium carbonate, and the amount of silane coupling agent was 0.3% of the mass of calcium carbonate.

[0092] (2) Preparation of modified Mg(OH)2 particles: 1 kg of Mg(OH)2 particles with a particle size of 3500-4500 mesh were dried at 105°C for 2 hours for later use. The dried Mg(OH)2 particles, aluminate and N,N'-ethylenebisoleamide surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 minutes to obtain modified Mg(OH)2 particles. The reaction temperature was controlled at 100°C. The amount of aluminate was 1.3% of the mass of Mg(OH)2, and the amount of N,N'-ethylenebisoleamide was 1.8% of the mass of Mg(OH)2.

[0093] (3) Preparation of modified inorganic antifungal and antibacterial agent: 0.5 kg of cuprous oxide was dried at 105° C. for 2 hours for later use. The dried cuprous oxide, borate ester and silane coupling agent were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 12 min to obtain a modified inorganic antifungal and antibacterial agent. The reaction temperature was controlled at 95° C. The amount of borate ester was 0.5% of the mass of cuprous oxide, and the amount of silane coupling agent was 0.6% of the mass of cuprous oxide.

[0094] (4) Preparation of modified laser absorber: 0.5 kg of phthalocyanine blue was dried at 105°C for 2 hours for later use. The dried basic copper phosphate and polyethylene wax surface modifier were added into a temperature-controlled high-speed mixer and mixed at a stirring rate of 600 r / min for 15 min to obtain the modified laser absorber. The reaction temperature was controlled at 90°C. The amount of polyethylene wax was 0.3% of the mass of the basic copper phosphate.

[0095] Preparation of anti-mildew, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch:

[0096] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 20 parts of modified CaCO3 particles, 51 parts of modified Mg(OH)2 particles, 2 parts of modified silver oxide, 5 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a blender and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0097] Example 5

[0098] The modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent and modified laser absorber prepared in Example 1 are used to prepare mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch:

[0099] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 20 parts of modified CaCO3 particles, 51 parts of modified Mg(OH)2 particles, 4 parts of modified silver oxide, 3 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0100] Example 6

[0101] The modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent and modified laser absorber prepared in Example 1 are used to prepare mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch:

[0102] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 30 parts of modified CaCO3 particles, 41 parts of modified Mg(OH)2 particles, 2 parts of modified silver oxide, 5 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a blender and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0103] Example 7

[0104] The modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent and modified laser absorber prepared in Example 1 are used to prepare mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch:

[0105] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 30 parts of modified CaCO3 particles, 41 parts of modified Mg(OH)2 particles, 4 parts of modified silver oxide, 3 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a blender and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0106] Example 8

[0107] The modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent and modified laser absorber prepared in Example 1 are used to prepare mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch:

[0108] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 40 parts of modified CaCO3 particles, 31 parts of modified Mg(OH)2 particles, 2 parts of modified silver oxide, 5 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0109] Example 9

[0110] The modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent and modified laser absorber prepared in Example 1 are used to prepare mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch:

[0111] According to the mass percentage, 14 parts of PC resin, 6 parts of ABS resin, 40 parts of modified CaCO3 particles, 31 parts of modified Mg(OH)2 particles, 4 parts of modified silver oxide, 3 parts of modified phthalocyanine blue, 0.6 parts of dispersant nonylphenol polyoxyethylene ether phosphate, 0.3 parts of antioxidant 2,6-di-tert-butyl-4-methylphenol, 0.5 parts of lubricant zinc stearate, and 0.6 parts of plasticizer triphenyl phosphate were added into a mixer and stirred at a speed of 600r / min for 25 minutes to mix evenly. Then the evenly mixed materials were added into a twin-screw extruder, and extruded and granulated at a temperature of 230°C, a current of 80A, and a pressure of 7MPa to obtain mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser carving masterbatch.

[0112] Comparative Example 1

[0113] The difference between Comparative Example 1 and Example 1 is that the CaCO3 particles are not surface modified, and the other operations are the same as those in Example 1.

[0114] Comparative Example 2

[0115] Compared with Example 2, Comparative Example 2 differs in that: the Mg(OH)2 particles are not surface modified, and other operations are the same as those in Example 2.

[0116] Comparative Example 3

[0117] Compared with Example 3, Comparative Example 3 differs in that the inorganic mildew and antibacterial agent is not surface modified, and other operations are the same as those of Example 3.

[0118] Comparative Example 4

[0119] Compared with Example 4, Comparative Example 4 differs in that: the laser absorber is not surface modified, and other operations are the same as Example 4.

[0120] Comparative Example 5

[0121] Compared with Example 5, Comparative Example 5 differs in that the CaCO3 particles and Mg(OH)2 particles are not surface modified, and other operations are the same as those in Example 5.

[0122] Comparative Example 6

[0123] Compared with Example 6, Comparative Example 6 differs in that the CaCO3 particles and the inorganic mildew and antibacterial agent are not surface modified, and the other operations are the same as those of Example 6.

[0124] Comparative Example 7

[0125] Compared with Example 7, Comparative Example 7 differs in that the CaCO3 particles and the laser absorber are not surface modified, and the other operations are the same as those of Example 7.

[0126] Comparative Example 8

[0127] Compared with Example 8, Comparative Example 8 differs in that the CaCO3 particles, Mg(OH)2 particles and the inorganic mildew and antibacterial agent are not surface modified, and the other operations are the same as those of Example 8.

[0128] Comparative Example 9

[0129] Compared with Example 9, Comparative Example 9 differs in that the CaCO3 particles, Mg(OH)2 particles and laser absorber are not surface modified, and other operations are the same as Example 9.

[0130] Take 40 parts of the products obtained in the above Examples 1 to 9 and Comparative Examples 1 to 9 respectively, mix them evenly with 30 parts of PC and 30 parts of ABS resin, and perform injection molding at 230° C. on an injection molding machine to prepare standard specimens and perform performance tests. The test results are shown in Table 1.

[0131] According to the national standards GB / T20944.3-2008, GB / T24346-2009, GB / T 2046-1993 and UL-94V, the antibacterial property, anti-mildew property, limiting oxygen index and vertical flame retardant property were tested. The test results are shown in Table 1.

[0132] Laser engraving effect test: Use a laser engraving machine to engrave patterns (power 500W, frequency 20KHz, laser wavelength 1064nm, laser engraving speed 1000mm / s). The laser engraving effect is determined based on the outline clarity and pattern depth. The laser engraving effect is represented by "☆". The more "☆", the better the laser engraving effect. The test results are shown in Table 1.

[0133] Table 1 Performance test results of samples prepared in Examples 1 to 9 and Comparative Examples 1 to 9

[0134]

[0135]

[0136] It can be seen from the test results in Table 1 that the modified Mg(OH)2 powder and the modified inorganic mildew and antibacterial agent are added to the PC / ABS alloy, which effectively improves the mildew and antibacterial properties of the PC / ABS alloy, and also improves the flame retardant grade and limiting oxygen index of the PC / ABS alloy. At the same time, the addition of the modified laser absorber enhances the laser carving effect of the PC / ABS alloy material and greatly reduces the application cost of PVC products. By comparing the results of Examples 1 to 9 with Comparative Examples 1 to 9, it can be seen that the unsurface-modified CaCO3 particles, Mg(OH)2 powder, inorganic mildew and antibacterial agent and laser absorber have unsatisfactory mildew and antibacterial properties, flame retardancy and laser carving effects on the PC / ABS alloy material; the reason is that the surface-modified Mg(OH)2 powder, modified silver oxide and phthalocyanine blue can be evenly dispersed in the PC / ABS alloy product, effectively synergistically improving the mildew and antibacterial properties, flame retardancy and laser carving effects of the PC / ABS alloy product.

[0137] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch, characterized in that: Prepared from the following raw materials in parts by weight: 20-70 parts of polycarbonate, 20-70 parts of acrylonitrile-butadiene-styrene plastic, 10-80 parts of modified CaCO3 particles, 10-75 parts of modified Mg(OH)2 particles, 1-5 parts of modified inorganic antifungal and antibacterial agent, 0.1-8 parts of modified laser absorber, 0.2-1.0 parts of dispersant, 0.1-0.5 parts of antioxidant, 0.1-1 parts of lubricant and 0.2-1.0 parts of plasticizer.

2. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 1, characterized in that: The preparation method of the modified CaCO3 particles comprises the following steps: mixing CaCO3 particles, a first surface modifier and a first lubricant to react to obtain modified CaCO3 particles; The first surface modifier includes one or more of a silane coupling agent, an aluminate, a titanate coupling agent, and a pentaerythritol stearate coupling agent; The first lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, stearic acid and zinc stearate; The mass ratio of the CaCO3 particles, the first surface modifier and the first lubricant is 100:0.3-1:0.5-2; The reaction temperature is 90-100° C., and the reaction time is 8-15 minutes.

3. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 2, characterized in that: The preparation method of the modified Mg(OH)2 particles comprises the following steps: mixing the Mg(OH)2 particles, the second surface modifier and the second lubricant to obtain the modified Mg(OH)2 particles; The second surface modifier includes one or more of a silane coupling agent, stearic acid, oleic acid, isocyanate, titanate and aluminate; The second lubricant includes one or more of N,N'-ethylene bisoleamide, N,N'-ethylene bisstearamide, polyethylene wax and zinc stearate; The mass ratio of the Mg(OH)2 particles, the second surface modifier and the second lubricant is 100:0.3-1.5:0.5-2; The reaction temperature is 90-110°C, and the reaction time is 7-15 minutes.

4. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to any one of claims 1 to 3, characterized in that: The preparation method of the modified inorganic antifungal and antibacterial agent comprises the following steps: mixing the inorganic antifungal and antibacterial agent with a third surface modifier to obtain the modified inorganic antifungal and antibacterial agent; The inorganic mildew and antibacterial agent includes one or more of titanium dioxide, tin dioxide, silver oxide, cupric oxide, cuprous oxide, copper sulfate, zinc oxide, and calcium phosphate; The third surface modifier includes one or more of a silane coupling agent, a titanate, an aluminate, a phosphate, an isocyanate, a borate, a zinc stearate and a polyethylene wax; The mass ratio of the inorganic mildew and antibacterial agent to the third surface modifier is 100:0.5-2.0; The reaction temperature is 90-100° C., and the reaction time is 6-15 minutes.

5. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 4, characterized in that: The preparation method of the modified laser absorber comprises the following steps: mixing the laser absorber with a fourth surface modifier to obtain the modified laser absorber; The laser absorbent includes one or more of carbon black, mica powder, basic copper phosphate, copper chrome black, tin oxide, titanium oxide, indium oxide, bismuth oxide, phthalocyanine blue and phthalocyanine green; The fourth surface modifier includes one or more of silane coupling agent, aluminate, titanate, phosphate, oleate, zinc stearate, and polyethylene wax; The reaction temperature is 90-100°C and the reaction time is 8-15 minutes; The mass ratio of the laser absorber to the fourth surface modifier is 100:0.3-1.

6. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 5, characterized in that: The dispersant includes one or more of sodium polyacrylate, nonylphenol polyoxyethylene ether phosphate, polyacrylamide, aminosilane and sodium dodecylbenzene sulfonate; The antioxidant includes one or more of tert-butylhydroquinone, tea polyphenols, 2,6-di-tert-butyl-4-methylphenol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, diisooctyl benzene phosphite, triphenyl phosphite and dioctyl benzene phosphite.

7. The mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 6, characterized in that: The lubricant includes one or more of N,N'-ethylene bisstearamide, N,N'-ethylene bisoleamide, polyethylene wax, paraffin, stearic acid and zinc stearate; The plasticizer includes one or more of dibutyl phthalate, dioctyl phthalate, di(2-ethylhexyl) phthalate, tricresyl phosphate, triphenyl phosphate and tri(2-ethylhexyl) phosphate.

8. The method for preparing the mildew-proof, antibacterial, halogen-free and flame-retardant PC / ABS laser engraving masterbatch according to any one of claims 1 to 7, characterized in that: The following steps are involved: Polycarbonate, acrylonitrile-butadiene-styrene plastic, modified CaCO3 particles, modified Mg(OH)2 particles, modified inorganic mildew and antibacterial agent, modified laser absorber, dispersant, antioxidant, lubricant and plasticizer are mixed and extruded to granulate to obtain mildew and antibacterial halogen-free flame-retardant PC / ABS laser engraving masterbatch.

9. The method for preparing a mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to claim 8, characterized in that: The granulation temperature is 210-250° C., the granulation pressure is ≤10 MPa, and the granulation current is 50-110A.

10. Use of the mildew-proof, antibacterial, halogen-free, flame-retardant PC / ABS laser engraving masterbatch according to any one of claims 1 to 7 in electronic product housings, switch covers / button labels, cosmetic packaging materials, automotive interior buttons and instrument panels, machine keyboards / buttons, or security anti-counterfeiting labels.

Citation Information

Patent Citations

  • Flame-retarding PC (Polycarbonate) / ABS (Acrylonitrile Butadiene Styrene) blend material for automobile interior trimmings and preparing method thereof

    CN103724967A

  • Laser direct structuring PC / ABScomposite material, preparation method and application thereof

    CN103923449A